Uso de microarray para determinação da expressão gênica diferencial em oócitos Bos Taurus Indicus e Bos Taurus Taurus submetidos ao estresse térmico - Ticianelli, Janahi Sousa [UNESP] (2014)
Genetic divergences in thermotolerance have been demonstrated between Bos taurus taurus (Holstein) and Bos taurus indicus (Nelore) animals. The deleterious effect of heat stress on oocyte developmental potential is greater for Bos taurus taurus as compared to Bos taurus indicus oocytes. Therefore, the present study determined transcriptome profile in Nelore and Holstein oocytes subjected heat shock during in vitro maturation (IVM) as well as mRNA abundance of selected candidate genes in Nelore and Holstein heat-shocked oocytes and cumulus cells. Non-lactating Holstein and Nelore cows were subjected to ultrasound-guided follicle aspiration during the cool season. Cumulus-oocyte complexes (COCs) were randomly assigned to control (38.5°C for 22 hours) and heat shock (41°C for 12 hours followed by 38.5°C for 10 hours) treatments during IVM. Denuded oocytes were subjected to Affymetrix bovine microarray. Genes with fold change of at least 1.5 and P< 0.05 were considered differently expressed. Microarray analyses demonstrated 127, 9 and 6 genes differentially expressed between Breed, Temperature and Breed x Temperature interaction, respectively. Selected differentially expressed genes were evaluated by RTPCR in oocytes and respective cumulus cells. There was a positive correlation between oocyte microarray and RT-PCR fold change for the genes KIF3A, CLDN11, BIRC3, DAP, MT1E, CCT4, DICER1 and DENND3. In particular, the member of the kinesin family 3A (KIF3A) gene was up-regulated in Holstein oocytes, while the deathassociated protein (DAP) and the protein trafficking gene DENN/MADD domain containing 3 (DENND3) were down-regulated in Holstein oocytes as compared to Nelore. The mRNA relative abundance of the antioxidant molecule metallothionein 1E (MT1E) was higher in Holstein cumulus cells, whereas, claudin 11 (CLDN11) that participates in cellular tight junctions, was higher in Nelore. Moreover, heat shock down regulated MT1E mRNA abundance ...